2019
DOI: 10.3389/fmech.2019.00014
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Tests Effect on Changes in the Surface Layers of Iron-Containing Antifrictional Aluminum Alloys

Abstract: Antifrictional properties and surface parameters of Al-Si-Cu-Sn-Pb alloys have been investigated. The effect of iron addition (∼1%) on the structure and tribological properties of aluminum alloy samples has been studied. Tribological properties were explored using the "shoe-roller" scheme with step-by-step pressure changes. The investigations were carried out both in and without a lubricant. The SEM-(with elemental analysis) and SPM-microscopy methods were applied to study sample surface and under-surface laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The results showed that the samples with high iron content had greater wear resistance and hardness, but the friction coefficient would be improved, demonstrating that the iron phase enhanced the wear resistance of recycled aluminum. 16,17 These studies have contributed to the application of plastic forming of recycled aluminum alloys in production. There has been a great deal of research on the production processes and intermetallic compounds, but little research has been conducted on the effects of recycled aluminum alloy defects on plastic forming.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the samples with high iron content had greater wear resistance and hardness, but the friction coefficient would be improved, demonstrating that the iron phase enhanced the wear resistance of recycled aluminum. 16,17 These studies have contributed to the application of plastic forming of recycled aluminum alloys in production. There has been a great deal of research on the production processes and intermetallic compounds, but little research has been conducted on the effects of recycled aluminum alloy defects on plastic forming.…”
Section: Introductionmentioning
confidence: 99%
“…One of the modern trends in materials design is the development of new antifriction aluminum alloys that can replace bronze in the manufacture of monometallic plain bearings [1,2,3,4,5]. The alloy material should have a wear resistance that is comparable with bronze resistance in friction contact with steel; and also steel counter body should wear weakly [6,7]. Replacing bronze with an aluminum alloy gives a noticeable economic effect, since aluminum is 2.5 times cheaper than copper in terms of unit weight and 3.3 times lighter than copper.…”
Section: Introductionmentioning
confidence: 99%